(Dis)comfort in the city: How young travellers in London negotiate mobility within the city. (August 2021) - Eales, Charlotte; Thomas, Huw
Abstract: Conflicting claims are made about the extent to which Travellers in Britain remain outsiders in urban society (McGarry 2017; Sibley 1981). This paper sheds light on this question by addressing a neglected aspect of Traveller mobility, namely the day-to-day traversing of urban spaces beyond their (typically segregated) trailer sites. Focusing on public transport, it draws on eighteen months of ethnographic research with young people from Traveller backgrounds from a London-based youth group to understand the nature of the encounters they have as they go out and about in the city. The paper is interested in the place of affect in these encounters, and more generally, affect's role in shaping – or failing to shape – young Travellers' behaviour. The paper considers discomfort experienced through the mobility of young Travellers; it argues that young Travellers are encouraged by their elders to discipline and regulate emotional responses in encounters with non-Travellers and that this constitutes evidence of their continuing outsider status. Highlights: Other passengers on public transport can create uncomfortable affective atmospheres. Young Travellers are largely insensitive towards these atmospheres. Travellers still see social interactions through a Traveller/non-Traveller binary. Training and guidance is provided by older Travellers for younger ones. This training involves navigating spaces, and their emotions, beyond the domestic.